2012
DOI: 10.3762/bjoc.8.231
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and biological evaluation of fluorinated cryptophycins

Abstract: SummaryCryptophycins are cytotoxic natural products that exhibit considerable activities even against multi-drug-resistant tumor cell lines. As fluorinated pharmaceuticals have become more and more important during the past decades, fluorine-functionalized cryptophycins were synthesized and evaluated in cell-based cytotoxicity assays. The unit A trifluoromethyl-modified cryptophycin proved to be highly active against KB-3-1 cells and exhibited an IC50 value in the low picomolar range. However, the replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…For unit B, the retention of d -tyrosine and benzene ring bearing para -methoxy or ortho -hydroxy is necessary for the activity. Studies showed that the B segment bearing the 5-fluorine substituted benzene ring lost bioactivity [ 99 , 104 ]. The C fragment structure-activity studies have focused on the C6 position, and it has been determined that the introduction of a bulky substituent such as a benzyl or isopropyl group resulted in a considerable reduction of bioactivity, while geminal methyl groups or a cyclopropyl group in the C6 position enhanced anticancer activity.…”
Section: Tubulin Inhibitors As Payloads Of Adcsmentioning
confidence: 99%
“…For unit B, the retention of d -tyrosine and benzene ring bearing para -methoxy or ortho -hydroxy is necessary for the activity. Studies showed that the B segment bearing the 5-fluorine substituted benzene ring lost bioactivity [ 99 , 104 ]. The C fragment structure-activity studies have focused on the C6 position, and it has been determined that the introduction of a bulky substituent such as a benzyl or isopropyl group resulted in a considerable reduction of bioactivity, while geminal methyl groups or a cyclopropyl group in the C6 position enhanced anticancer activity.…”
Section: Tubulin Inhibitors As Payloads Of Adcsmentioning
confidence: 99%
“… “The product was obtained in enantiomerically pure form as shown by HPLC”, is stated in ref ,. but no numerical value is given.…”
Section: γ‐Lactone Synthesis By the Sharpless Asymmetric Dihydroxymentioning
confidence: 93%
“…The cytotoxic macrocyclic depsipeptide cryptophycin‐52 ( 300 , R = H) and its unnatural analogues 301a – d were synthesized in Scheme . The hydroxylactone motif ( 101 , 297a – d ) was established early on by the SAD strategy.…”
Section: The Sharpless Asymmetric Dihydroxylation Of βγ‐Unsaturatmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptophycin‐52 analogs with more than one fluorine substituent have recently been published (Figure ) . The CF 3 ‐functionalized compound is about fivefold less active against the tumor cell line KB‐3‐1 in comparison with cryptophycin‐52, while the pentafluorophenylalanine analog shows a significant loss of cytotoxicity, most likely owing to the absence of the methoxy group.…”
Section: Fluorinated Cryptophycinsmentioning
confidence: 99%